Myographic analysis of the upper limb muscle response to physical exercises in patients with acute stroke - B. I. Vakhitov; I. S. Raginov; I. Kh. Vakhitov; R. N. Kashapov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
We analyzed the results of examination of 85 patients with ischemic stroke in the carotid arterial system and leading hemiparesis syndrome during the early recovery period. The experimental group included 51 males and 34 females aged between 42 and 65 years (mean age 57.3 years). The control group comprised 20 healthy individuals matched for age and gender. This study was undertaken to assess the appropriateness of activation and coordination relationships in muscles of patients in the early recovery period after ischemic stroke in the carotid arterial system depending on its severity. We measured the amplitudes of the maximum arbitrary activity of the shoulder, forearm, and hand antagonist muscles using EMG and calculated adequacy coefficient (AC) and reciprocity coefficient (RC) (both sides). All patients were divided into two groups according to their Barthel index. Group 1 included 29 patients with mild restrictions in their daily living, whereas Group 2 included 56 patients with moderate restrictions in their daily living. All study participants had mild to moderate hemiparesis (with muscle strength of 3–4. 5 points). In Group 1, we registered increased RC (to 104%) in the forearm extensors and increased AC (to 85%) in the forearm flexors on the paresis side. In Group 2, we observed increased RC in the shoulder flexors and forearm extensors (to 89%) and increased AC in the shoulder extensors (to 76%) on the paresis side. Patients from Group 1 demonstrated high RC (68%) and AC (53%) in nonparetic limbs. Patients from Group 2 demonstrated even higher RC and AC (72%) in nonparetic limbs. Surface EMG with AC and RC calculation objectifies both the severity of paresis and tone disorders in paretic and nonparetic limbs. This method can also be used to predict the degree of motor defect recovery and evaluate the effectiveness of rehabilitation in patients with mild to moderate disease and predominant central hemiparesis syndrome.